Towards a vocational education ecosystem framework: A systematic literature review of industry partnership, curriculum alignment, educational financing, and employability in SMK and TVET - Sungkem Tri Wahyuni; Nurul Astuti Yensy; Sudarwan Danim (Journal of Advanced Sciences and Mathematics Education, 2026)
Background: Vocational education and training (SMK and TVET) are expected to reduce skills mismatch and improve employability. However, many reforms remain fragmented because industry partnership, curriculum alignment, educational financing, and employability are often treated as separate issues rather than interconnected dimensions within a vocational education ecosystem. Aims: This study aims to develop a Vocational Education Ecosystem Framework (VEEF) explaining how industry partnership, curriculum alignment, educational financing, and employability interact systematically in SMK and TVET. Methods: The study employs a Systematic Literature Review (SLR) with a critical-interpretive synthesis orientation. Scopus-indexed journal articles published between 2021–2026 were identified, screened, and synthesised using PRISMA procedures, explicit selection criteria, and thematic analysis. Results: The findings show that industry partnership functions as a governance mechanism connecting institutions, firms, and labour markets. Curriculum alignment acts as a translational mechanism linking labour-market needs with pedagogy, assessment, certification, and teacher capability. Educational financing serves as enabling infrastructure supporting implementation quality, innovation, access, and sustainability. Employability emerges as a systemic outcome shaped by the interaction among governance, curriculum, and resource configuration. These relationships form the basis of VEEF, consisting of Governance, Translational, Resource, and Outcome nodes. Conclusion: Effective SMK and TVET systems depend on strong ecosystem integration rather than isolated interventions. VEEF offers a comprehensive conceptual foundation for understanding vocational education reform and sustainable school-to-work transitions.